1986
DOI: 10.1007/bf02431623
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Zr-Ni metallic glasses

Abstract: The crystallization of Zr-Ni metallic glasses of composition between 55 and 70at% Zr has been investigated using differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The samples were prepared by splat quenching in an arc-hammer device. Transformation temperatures, effective activation energies, and enthalpy changes are reported as a function of composition. Results of XRD patterns obtained as a function of annealing temperature in the DSC are presented. A high temperature exothermic DSC peak an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For sintered samples, crystalline reflections appear overlaid the broad peaks of the amorphous phase. For G5, the main phase produced by devitrification is the metastable Ni 2 Zr 3 , [22] in equilibrium with tetragonal NiZr 2 , orthorhombic NiZr, and monoclinic ZrCu. Orthorombic Al 5 Ti 3 , metastable Ni 2 Zr 3 , tetragonal NiZr 2 and tetragonal CuZr 2 have been identified as the crystalline phases in G2.…”
Section: Resultsmentioning
confidence: 99%
“…For sintered samples, crystalline reflections appear overlaid the broad peaks of the amorphous phase. For G5, the main phase produced by devitrification is the metastable Ni 2 Zr 3 , [22] in equilibrium with tetragonal NiZr 2 , orthorhombic NiZr, and monoclinic ZrCu. Orthorombic Al 5 Ti 3 , metastable Ni 2 Zr 3 , tetragonal NiZr 2 and tetragonal CuZr 2 have been identified as the crystalline phases in G2.…”
Section: Resultsmentioning
confidence: 99%
“…6(a) for amorphous alloys formed by meltquenching. Later, Altounian et al [20] and McKamey et al [21] reported enthalpy of crystallization data of the same magnitude for Ni-rich alloys, but slightly (by about 1-2 kJ mo1-1) smaller on the Zr-rich side. The final crystallization products have been confirmed to be the equilibrium compounds [20].…”
Section: Experimental Datamentioning
confidence: 85%
“…Amorphous Zrl_~Mx alloys have been formed only by mechanical alloying of elemental Zr and A1 powders [17][18][19]. Amorphous Zr-Ni alloys on the other hand, have been formed by a variety of techniques [6(a), [20][21][22][23][24][25]. In Section 2 we first discuss the experimental enthalpy of crystallization data for amorphous Zrl_~klx and Zrl_xNix alloys, determined from calorimetric measurements, and convert them into enthalpy of formation data using the known enthalpy of formation for equilibrium compounds [6].…”
Section: E Ma M Atzmon / Zrt_alx and Zrl_xnix Alloysmentioning
confidence: 99%
“…These samples exhibit broad peaks, characteristic of nanocrystalline phases. For G5, the main phase is Ni 2 Zr 3 metastable [27] in equilibrium with tetragonal NiZr 2 , orthorhombic NiZr and monoclinic CuZr. Crystalline phases in G2 are orthorhombic Al 5 Ti 3 , metastable Ni 2 Zr 3 , tetragonal NiZr 2 and tetragonal CuZr 2 .…”
Section: Sps Of Mg Powdermentioning
confidence: 99%